THE PECULIARITIES OF GENDER IN PAREMIAS - Qarayeva Mavjuda Yoqubjonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article studies specific peculiarities of gender and its communicative impact to the meaning of paremias in English and uzbek languages.